พระนเรศวร : วาทกรรมจากอดีตที่แปรเปลี่ยนไปสู่วาทกรรมเชิงสัญลักษณ์แห่งกองทัพบกไทย - เฉลิมพล แซ่กิ้น (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The main objective of this dissertation is to view the stories of king Naraesuan as symbolic power in the Royal Thai army. The fundamental hypothesis of this study is the stories or discourses of king Naraesuan have been periodically transforming with respect to the sociological and political context in each era. The methodology employed in this study is called Genealogy of Michel Foucault. It is, in other word, to trace back into the stories or discourses of King Naraesuan of how their identities have been produced and developed into the society and for whom and of what expectation on their exercises. It is shown after the study that the stories of King Naraesuan have been modified era by era by the power-possessing persons or elites determining and inserting principles into the stories to meet their desire. Such phenomenon has existed up until the present era when the Royal Thai Army has seized the political power.